A RARE CASE OF HOLOACARDIUS ACEPHALUS MONSTER IN A BUFFALO - PANDE, NISHI; AGRAWAL, R G; SHRIVASTAVA, O P; SHUKLA, S N (The Indian Journal of Animal Reproduction, 2023)
The present communication reports a rare case of Holoacardius acephalus monster in a buffalo.